Implementing OKR in Indonesian Public Bureaucracy: A Case Study of the Ministry of State Secretariat - Wulansari, Nita; Prasojo, Eko (Jurnal Administrasi Publik (Public Administration Journal), 2025)
This study aims to examine the compatibility of Objective and Key Results (OKR) as a performance management framework in the context of public bureaucracy, with a case study at the Ministry of State Secretariat. Using a qualitative approach, this study analyzes the application of the basic principles of OKR, the advantages and disadvantages that arise, and the implementation challenges faced. The results of the study indicate that the success of OKR adoption is highly dependent on the organization's contextual awareness, namely the ability to adapt the design and implementation of OKR to the existing structure, work culture, and regulatory system. OKR provides a number of advantages such as increased performance tracking, employee performance diversification, collective alignment and accountability, flexibility, and frequency of performance monitoring and evaluation, thereby increasing the perception of fairness among employees. However, there are also weaknesses such as the tendency for OKR to become a to-do list, incompatibility with certain types of work, and insynchrony with the performance compensation system. Other challenges include HR capacity, work culture transformation, performance-based reward systems, consistency in the review and monitoring process, and coordination between agencies, and the need for a sustainable digital support system. Despite the growing popularity of OKR in private sector organizations, empirical studies examining the adaptation and effectiveness of OKR in public sector bureaucracies, particularly in developing country contexts, are still very limited. Therefore, this study contributes to the public administration literature by providing contextual empirical findings on how OKR interacts with bureaucratic characteristics, regulatory frameworks, and government organizational culture in Indonesia. These findings emphasize that OKR cannot be adopted uniformly in the public sector, but needs to be implemented gradually and adaptively.